Design and Analysis of a Novel Four-DOF Parallel Robot Mechanism - Zou Ye; Huang Zhihui; Tang Liping (Jixie chuandong)
A novel fully-decoupled three-translational and one-rotational（ 3T1R） parallel robot mechanism is proposed. First,the degree of freedom analysis and instantaneous analysis of the parallel mechanism is carried out by using the screw theory and the correctness of the configuration method is verified.Through the analysis of the relationship between input and output of mechanism,the Jacobian matrix of the parallel mechanism is obtained and it is 4 × 4 order diagonal matrix. The fully-isotropic and fully-decoupled characteristics of the mechanism are proved. And this mechanism control is simple and has good movement and force transmission performance and higher practical value.